Analisis Peran Lingkungan Kerja dan Gaya Kepemimpinan terhadap Kinerja Karyawan pada Divisi Produk Pakaian Pria Uniqlo Indonesia - Pande Nanda Dwi Hyunita; Pebriansyah Pebriansyah (Jurnal Ilmiah Manajemen, Ekonomi dan Akuntansi, 2026)
The success of employee performance is not only limited to the training and education they have, but also several aspects related to employee achievement and productivity are one of the keys to success that greatly influence company performance. This study aims to determine the role of the work environment and leadership style on employee performance in the men's clothing division of Uniqlo Indonesia. This study was conducted using descriptive qualitative research involving books, journals, and scientific articles relevant to the research conducted by the author. In addition, the author also conducted field observations to determine the application of leadership styles and employee performance in the men's clothing division of Uniqlo Indonesia. The results of the study indicate that there is a close relationship between leadership style and work environment on employee work productivity related to the application of Japanese culture which is disciplined and has loyalty to the company. The combination of factors related to the environment and leaders creates an efficient and adaptive work pattern related to market changes that occur.